A transmutação monadológica de Björk: tradução intersemiótica da dor em três dimensões, a partir de Black Lake - Nunes, Jefferson Cândido (2017)
Björk goes beyond creativity with her unique art and thus has innovated and influenced important media sectors, such as the music, the photographic and digital art, and the video making industries. With her latest album, Vulnicura (BJÖRK, 2015n), the Icelandic artist expresses a keen sense of pain that reaches its apex in Black Lake (2015c), the fourth track of the disc. From the poetic text, composed by the lyrics of that song, I investigate how the transmutation of Björk’s subjectivity happened through the intersemiotic translation of that text-sign to three different polysystems: music, image and video. Therefore, I propose a dialogue, among others, with the studies of Jakobson (1992), Plaza (2003) and Pierce (2000), who have important works on intersemiotic translation, to compose the first part of the theoretical foundation of this research. In addition, I ground it in the investigations of Kühl (2008), Barthes (1977) and Goodwin (1992), who deal, respectively, with media translations to music, image and video, to compose the specific elements of analysis of the corpus here studied and, along with other authors, to be able to analyze it from a more heterogeneous theoretical framework. The results point to the mastery of Björk by evidence of her artistic ability to uniquely transmutate the sensation of pain – and, by extension, to transcreate her own self – to those three sign dimensions, reinforcing such an element in her translations. It follows, therefore, that this research is relevant to the development of the Translation Studies and, more specifically, to provide better understanding of phenomena concerning the intersemiotic translation.